System Security for Motorcycle with Arduino - Andi Muhammad Nur Nurhidayat; Muhammad Nur Akbar (Universitas Muhammadiyah Makassar, 2020)
Nowadays, vehicles are the main requirement for carrying out activities of daily life. One of the most widely used by Indonesians is motorbikes. The motorcycle safety system provided by motorcycle manufacturers has not been effective and still has many shortcomings. Besides, the rampant motorcycle thief and robbery cases have made vehicle owners have to pay attention to their motorbikes' safety. An integrated motorcycle safety system is much needed. The design of a motorcycle vehicle system that is integrated with the Arduino via Bluetooth media provides quite maximum test results. Based on the results of testing, the accuracy of the tool gives 99% results. This safety system can turn off and turn on the motorcycle stock contact automatically. When the motorbike is on, Bluetooth on the motorbike and Bluetooth on the helmet are separated beyond a distance of 10 meters, the stock contact on the motorcycle vehicle will turn off so that the motorbike cannot be turned on at the same time the alarm will flash. The motor can be turned on after Bluetooth on the helmet, and the motorbike is connected or reconnected. With this, the safety standards on motorbikes are getting better. Motorcycle users will feel safe after leaving their vehicle.